85 QUALITY IMPROVEMENT INITIATIVE TO ASSESS FRAILTY AWARENESS AND USE CLINICAL FRAILTY SCALE AMONGST STAFF IN ACUTE AND PRIMARY CARE SITES. (25th October 2022) - Sweeney, M; Thomas, I; OReilly, A; Duggan, J; Conaty, J; Smith, B; Enaeney, AM; Tackney, L; Hopkins, C; O'Reilly, R
Abstract: Background: Frailty describes a condition characterized by decreased physiological reserve and a decreased resistance to stressors, leading to an increased vulnerability to adverse outcomes. Identification of frailty can generate greater complexity in treatment choices, care planning, and costs of care. Methods: 30 inpatient, Emergency Department and Ambulatory Hub charts were audited to assess the presence of the word Frailty. The use of the Clinical Frailty Scale or alternative frailty scale was also audited. A staff survey was completed across four sites, a total of 115 staff were surveyed. Results: Awareness of frailty across all services is very good ranging from 92% to 100%. The use and awareness of the Clinical Frailty Scale varied with 41% Emergency department and 12% of acute staff respectively but only 25% Emergency Department and 12% of acute staff feeling competent to complete the scale. Conversely, there was a 73% awareness of the Clinical Frailty Scale amongst primary care staff, 33% feeling competent in it's use. The Ambulatory Hub had 100% awareness of the scale with 54% of staff feeling competent. The chart audit showed that 20% of charts in the Emergency Department identified frailty, all by the Frailty Intervention Team. 26% of the inpatient charts identified Frailty by the Frailty Intervention Team's notes and from one visiting consultant. Frailty was identified and measured using the Clinical Frailty Scale in all cases of the Ambulatory Hub notes. Conclusion: By identifying frailty at the first point of contact, targeted specialist interventions and services can be planned for the service user. Frailty identification on the acute site was mainly linked to the Frailty Intervention Team with the Ambulatory Hub leading out on frailty identification and measurement in the community. Future initiatives aim to increase frailty identification and awareness in acute and primary care sites.